Pengaruh Pemberian Daun Lamtoro (Leucaena leocephala) terhadap Kualitas Silase Rumput Gajah (Pennisetum purpereum) yang Diberi Molasses - M. Yunus (Agricultural Faculty, 2009)
The effect of gift lamtoro leaf (Leucaena leocephala) to quality of silage of elephant grass (Pennisetum purpereum) that adding molassesABSTRACT. Research about the effect of gift of lamtoro leaf and molasses to quality of elephant grass silage (Pennisetum purpereum) have been executed at Lamsiot village Indrapuri sub district Aceh besar. Analysis content of nutrient in Food Livestock laboratory Agriculture Faculty of Syiah Kuala University. This research aim to see how influence of gift lamtoro leaf and elephant grass silage that adding molasses. This research the complete random device consisted o with 5 kinds of treatment and 3 restarting. This is R1 silage control without treatment and lamtoro leaf 0 5. R2 silage without lamtoro leaf (0%) and molasses 5%, R3 silage with the addition of lamtoro leaf 10%, R4 20%, R5 30%, adding molasses each 5%. The parameter of this study is acidity (pH) degree (pH), dry matter, crude protein, and crude fiber. to know the treatment influence used data Analysis and continued with the Duncan Test. The result of this research indicated that gift of lamtoro leaf give the real influence at pH and influence with is not real at dry substance, while at crude protein and crude fiber give the very real influence. Best silage there are at silage with 30% of lamtoro leaf.